Maisonneuve fractures and ligament injuries: how to stabilize the ankle? - Pansini, José Vicente; Augusto Baggio Pereira, Cesar; dos Santos Batista, Flamarion; Muratore Thaddeu, Eduardo; Sell Poletto, Rodrigo; Heloisa Breidenbach Pupim, Barbara (Journal of the Foot & Ankle, 2025)
Objectives: Quantify syndesmosis and deltoid injuries in Maisonneuve Fractures, identify which ligament is the most efficient in ankle stabilization, quantify the need for joint ligament repairs, and certify the ankle stability without fracture fixation. Methods: Between 2007 and 2022, a total of 70 patients were included-40 with acute trauma and 30 with chronic trauma; the mean age was 35.57 years. Fifty-one patients were randomized into Groups I and II. Patients in Group I (26) received syndesmosis repair, and patients in Group II (25) received deltoid repair. Group I also received a deltoid suture when the patients were still unstable, and Group II received syndesmosis repair. Chronic patients, in addition to fixation, also received syndesmosis reconstruction. Results: Ligament injuries were present in 100% of the ankles, 72.86% joint injuries, and 27.14% isolated. Syndesmosis repair stabilized 61 ankles (92.42%), and deltoid repair nine ankles (16.98%). Joint repairs were performed on 28 ankles (40%). Stable ankles without fibular fracture fixation totaled 68 (97.15%). The syndesmosis repair in Group I was efficient in 80.76%, and in Group II, the deltoid repair in 13.73%. In non-randomized patients (19), 100% of the repairs alone were efficient. Conclusion: Our results concluded that the Maisonneuve fractures had 100% associated ligament injuries. Fixing the syndesmosis was significantly more efficient than repairing the deltoid in stabilizing the ankle. Repairs of both ligaments were necessary in 40% of the ankles. Stabilizing the ankle does not require addressing the high fibular fracture. Level of Evidence IV; Therapeutic studies - investigating the results of treatment; Case Series.